Evaluation of Exotically-Derived Soybean Breeding Lines for Seed Yield, Germination, Damage, and Composition under Dryland Production in the Midsouthern USA - Bellaloui, Nacer; Smith, James R.; Mengistu, Alemu; Ray, Jeffery D.; Gillen, Anne M. (Frontiers in Plant Science, 2017)
Although the Early Soybean Production System (ESPS) in the Midsouthern USA increased seed yield under irrigated and non-irrigated conditions, heat stress and drought still lead to poor seed quality in heat sensitive soybean cultivars. Our breeding goal was to identify breeding lines that possess high germination, nutritional quality, and yield potential under high heat and dryland production conditions. Our hypothesis was that breeding lines derived from exotic germplasm might possess physiological and genetic traits allowing for higher seed germinability under high heat conditions. In a two-year field experiment, breeding lines derived from exotic soybean accessions, previously selected for adaptability to the ESPS in maturity groups (MG) III and IV, were grown under non-irrigated conditions. Results showed that three exotic breeding lines had consistently superior germination across two years. These lines had a mean germination percentage of greater than 80%. Two (25-1-1-4-1-1 and 34-3-1-2-4-1) out of the three lines with ≥80% germination in both years maintained high seed protein, oleic acid, N, P, K, B, Cu, and Mo in both years. Significant (P < 0.05) positive correlations were found between germination and oleic acid and with K and Cu in both years. Significant negative correlations were found between germination and linoleic acid, Ca, and hard seed in both years. There were positive correlations between germination and N, P, B, Mo, and palmitic acids only in 2013. A negative correlation was found between germination and green seed damage and linolenic acid in 2013 only. Seed wrinkling was significantly negatively correlated with germination in 2012 only. A lower content of Ca in the seed of high germinability genotypes may explain the lower rates of hard seed in those lines, which could lead to higher germination. Many of the differences in yield, germination, diseases, and seed composition between years are likely due to heat and rainfall differences between years. The results also showed the potential roles of seed minerals, especially K, Ca, B, Cu, and Mo, in maintaining high seed quality. The knowledge gained from this research will help breeders to select for soybean with high seed nutritional qualities and high germinability.